Screening of active components of melastoma dodecandrum lour. against diabetic osteoporosis using cell membrane chromatography-mass spectrometry - Zhang, Xiaoqin; Mao, Jiale; Shao, Lu; Liu, Shuang; Zhou, Jiwang; Mei, Mingrong; Zhang, Zunjing (Frontiers in Pharmacology, 2024)
Background Melastoma dodecandrum Lour. (MD), a traditional botanical drug known for its hypoglycemic, antioxidant, and anti-inflammatory properties, is commonly used to treat diabetes, osteoarthritis, and osteoporosis. However, its specific active components against diabetic osteoporosis remain unclear. Purpose This study aimed to identify the key active components in MD using cell membrane chromatography coupled with mass spectrometry and validate their effects in vitro. Methods An AGEs-induced osteoblast injury model was established. MTT assays measured cell viability, and ALP activity was assessed using a biochemical kit. Western blotting was employed to detect the expression levels of osteoblast-related proteins OCN and RUNX2 and the AGE receptor protein RAGE. ELISA was used to determine the levels of SOD, MDA, CAT, and GPx. PCR quantified TNF-α expression to evaluate the protective effects and potential mechanisms of MD. The AGEs-induced osteoblast cell membrane chromatography-mass spectrometry method facilitated the rapid identification of potentially active compounds based on their affinity for the osteoblast cell membrane. Cell experiments further validated the activity of the characteristic component isovitexin. Results MD significantly improved cell viability in AGEs-damaged osteoblasts, enhanced ALP, SOD, CAT, and GPx activities, reduced MDA levels, increased OCN and RUNX2 protein expression, and decreased TNF-α mRNA and RAGE protein expression. Cell membrane chromatography identified 20 chemical constituents, including 13 flavonoids, 4 organic acids, 1 phenylpropanoids, 1 terpenoids, and 1 alkaloid. Cell experiments have confirmed that isovitexin has significant protective activity against osteoblasts and can inhibit the expression of specific receptor RAGE on the osteoblast membrane, consistent with the effect of MD. Conclusion MD and its active component, isovitexin, provide protective effects against AGEs-induced osteoblast injury, offering a basis for subsequent drug development.